2010
DOI: 10.1038/ja.2010.142
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of common intermediate 3-hydroxy-L-kynurenine in chromophore biosynthesis of quinomycin family antibiotics

Abstract: Quinomycin antibiotics, represented by echinomycin, are an important class of antitumor antibiotics. We have recently succeeded in identification of biosynthetic gene clusters of echinomycin and SW-163D, and have achieved heterologous production of echinomycin in Escherichia coil. In addition, we have engineered echinomycin nonribosomal peptide synthetase (NRPS) to generate echinomycin derivatives. However, the biosynthetic pathways of intercalative chromophores quinoxaline-2-carboxylic acid (QXC) and 3-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Successful incorporation of 6a and 7a into 1 and 4 strongly indicated that L-tryptophan is converted to 3-hydroxykynurenine (7) as a common precursor in the biosynthesis of two different chromophores (QXC and HQA). 9,10 Enzymatic conversions of 7 to 9 via transamination product 10 with Swb1 and Swb2 provide further support to this hypothesis. 10 Based on the general mechanism of NRPS (colinearity rule) as shown above, amino acid specificity of the deduced adenylation (A) domain from the amino acid sequence and organization of ecm NRPS provide information on the reaction pathway of the peptide core formation (Scheme 2).…”
Section: Enzymatic Synthesis Of Echinomycin and Its Derivativessupporting
confidence: 62%
See 1 more Smart Citation
“…Successful incorporation of 6a and 7a into 1 and 4 strongly indicated that L-tryptophan is converted to 3-hydroxykynurenine (7) as a common precursor in the biosynthesis of two different chromophores (QXC and HQA). 9,10 Enzymatic conversions of 7 to 9 via transamination product 10 with Swb1 and Swb2 provide further support to this hypothesis. 10 Based on the general mechanism of NRPS (colinearity rule) as shown above, amino acid specificity of the deduced adenylation (A) domain from the amino acid sequence and organization of ecm NRPS provide information on the reaction pathway of the peptide core formation (Scheme 2).…”
Section: Enzymatic Synthesis Of Echinomycin and Its Derivativessupporting
confidence: 62%
“…9,10 Enzymatic conversions of 7 to 9 via transamination product 10 with Swb1 and Swb2 provide further support to this hypothesis. 10 Based on the general mechanism of NRPS (colinearity rule) as shown above, amino acid specificity of the deduced adenylation (A) domain from the amino acid sequence and organization of ecm NRPS provide information on the reaction pathway of the peptide core formation (Scheme 2). 5 Experimental results on a chromophore activating enzyme and an acyl carrier protein in the triostin biosynthesis suggest that QXC is activated and loaded onto NRPS Ecm6 by the catalysis of Ecm1 and FabC for fatty acid biosynthesis.…”
Section: Enzymatic Synthesis Of Echinomycin and Its Derivativessupporting
confidence: 62%
“…Several antibiotics can be derived from the kynurenine pathway, including sibirimycin, which arises from a modified pathway involving a methylation step (Giessen et al, 2011 ), and actinomycin, whose synthesis involves an additional set of some enzymes of this pathway, apart from the “normal” kynurenine pathway (Keller et al, 2010 ). Tryptophan dioxygenase is also implicated in the production of quinomycin antibiotics via a β-hydroxy-kynurenine intermediate (Hirose et al, 2011 ).…”
Section: The Biosynthesis Of Aaamentioning
confidence: 99%
“…Loss of this formyl moiety can be spontaneous, or other enzymes could be involved in this (TioL, TioM, TrsF, Ecm14, Qui3) [15,43]. The resulting molecule, β-hydroxykynurenine, has been used in successful feeding experiments, demonstrating its existence in this biosynthetic pathways [47]. Up to this point, these l -Trp modifications are somehow similar to those produced during formation of kynurenine in liver and other vertebrate organs, where it is a key intermediate of NADH [15,48].…”
Section: Modular Biosynthesis In the Bisintercalators Familymentioning
confidence: 99%
“…β-hydroxykynurenine is a common intermediate in these two biosynthetic pathways [47]. This compound is the substrate of an aminotransferase (TioG, Swb1), which generates the bicyclic heteroaromatic intermediate 3,4-dihydroxy-quinaldic acid (Scheme 6), which is further transformed by the action of an oxidoreductase (TioH, Swb2) into 3HQA [15].…”
Section: Modular Biosynthesis In the Bisintercalators Familymentioning
confidence: 99%